Second victim syndrome and turnover intention among critical care nurses - Sulaiman Al Sabei; Mohammed Qutishat (Discover Mental Health)
Abstract Background Second victim syndrome (SVS) significantly affects healthcare professionals, particularly staff nurses working in critical care units, who often encounter traumatic events at work. This emotional turmoil can lead to increased turnover intention, posing challenges to workforce stability and patient care quality. Therefore, this study examined the relationship between the SVS and turnover intention among staff nurses working in critical care units. Method This study used a descriptive cross-sectional design. Staff nurses in Oman completed self-administered adopted questionnaires including the Second Victim Experience and Support Survey, and the Turnover Intention Scale. Data were collected between April and June 2024. Results A sample of 199 staff nurses participated in the study. The study revealed that most respondents had a moderate level of SVS (61.31%, n = 122). Approximately half of the respondents (50.25%, n = 100) reported a lower level of turnover. The results indicated that higher levels of SVS were positively and significantly associated with higher turnover intention (β = 0.18, SE = 0.012, p = 0.001, CI [0.007–0.055]). Conclusion This study revealed a significant connection between SVS and staff nurses working in critical care units’ intentions to leave their jobs in Oman, driven by emotional distress and inadequate support. Addressing these issues is vital for improving nurse retention and quality of patient care.